1990
DOI: 10.1016/0735-1097(90)90327-l
|View full text |Cite
|
Sign up to set email alerts
|

Lysis of plasminogen activator-resistant platelet-rich coronary artery thrombus with combined bolus injection of recombinant tissue-type plasminogen activator and antiplatelet GPIIb/IIIa antibody

Abstract: Resistance of coronary occlusive thrombus to thrombolytic therapy, found in some patients with acute myocardial infarction, may be due to the presence of platelet-rich coronary clot. Reperfusion therapy in such patients may require the development and evaluation of alternative strategies in animal models. Therefore, platelet-rich coronary artery thrombus was developed by excision, eversion (inside out) and reanastomosis of a 1 cm segment of the left circumflex coronary artery in anesthetized dogs maintained on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(48 citation statements)
references
References 20 publications
4
43
0
1
Order By: Relevance
“…530 Neither fosphenytoin nor sipatrigine has demonstrated effectiveness in treatment of acute stroke. 531,532 Repinotan, a serotonin agonist, has shown some promise in preliminary studies. 533 Lubeluzole was tested in several clinical trials, including one that evaluated the combination of the medication and rtPA.…”
Section: Neuroprotective Agentsmentioning
confidence: 99%
“…530 Neither fosphenytoin nor sipatrigine has demonstrated effectiveness in treatment of acute stroke. 531,532 Repinotan, a serotonin agonist, has shown some promise in preliminary studies. 533 Lubeluzole was tested in several clinical trials, including one that evaluated the combination of the medication and rtPA.…”
Section: Neuroprotective Agentsmentioning
confidence: 99%
“…13,14 In acute coronary syndrome, obstructive arterial thrombi that are platelet rich are resistant to thrombolysis and have an increased tendency to reocclude after initial reperfusion. 16 In these circumstances, an antiplatelet agent used in combination with a thrombolytic agent not only offers the potential for enhancing thrombolysis and reducing the risk of reocclusion but also permits this to be accomplished with reduced doses of thrombolytics and heparin. 17 Therapeutic decisions with regard to clot composition may facilitate thrombolysis and reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] Cumulatively, these studies have shown that the dose of fibrinolytic therapy can be substantially reduced to Ϸ50% or even 25% of the dose required in control experiments 57,58 and that fibrinolysis occurs much more rapidly and more completely and is much more stable, as reflected by the absence of cyclic flow variations or reocclusion once flow is restored. Nicolini and associates 65 showed that a low dose of a GP IIb/IIIa inhibitor combined with a low dose of a direct thrombin inhibitor (hirudin) also markedly facilitated coronary fibrinolysis in the canine electrolytic model.…”
Section: Experimental Studiesmentioning
confidence: 99%